New Insights into the Relationship between Viral Infection and Pregnancy Complications - Kwon, Ja-Young (Am J Reprod Immunol, 2014)
A recent study by McDonnold and co-investigators published in the American Journal of Obstetrics and Gynecology reports an association between human papillomavirus (HPV) infection and preeclampsia. The investigation was based on the hypothesis that HPV trophoblast infection results in failed trophoblast invasion, and placental dysfunction and hypoxia. The ﬁndings from this study along with previous data addressing the relationship between viral infection and obstetrical complications highlight the relevance of viral infection during pregnancy. A better understanding of mechanisms via which virus leads to pregnancy complications will drive us closer to ﬁnding a strategy to prevent adverse outcomes.